Vitamin and mineral requirements in human nutrition (Geneva, 2004)
The Joint FAO/WHO group of experts reviewed the full scope of vitamin and minerals requirements, including their role in normal human physiology and metabolism and in deficiency disease conditions. The focus was on the requirements of the essential vitamins and minerals, including vitamins A, C, D, E, and K; the B vitamins; calcium; iron; magnesium; zinc; selenium; and iodine. The report provides recommended nutrient intakes for vitamins A, C, D, E, and K; the B vitamins; calcium; iron; magnesium; zinc; selenium; and iodine. The report also provides practical advice and recommendations which will constitute an authoritative source of information for all those who work in the area of nutrition, agriculture, food production and distribution, and health promotion.
Keywords: Khoáng chất trong dinh dưỡng con người,Vitamins in human nutrition,Minerals in human nutrition,Vitamin trong dinh dưỡng con người